2022
DOI: 10.3390/su142114097
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Multifunctional Self-Expanding Electrospun Polyacrylic Acid Covalently Cross-Linked Polyamide 66 Nanocomposite Fiber Membrane with Excellent Oil/Water Separation and High pH Stability Performances

Abstract: In this paper, we report for the first time the successful formation of a covalent cross-linking structure between polyacrylic acid and polyamide 66 in an electrospun nanofiber membrane by the facilitated amidation reaction using N-Hydroxy-succinimide (NHS) and N-(3-Dimethylaminopropyl)-N’-ethyl-carbodiimide hydrochloride (EDC). The structure and properties of the fiber membrane are characterized using scanning electron microscopy, wide field X-ray diffraction and differential scanning calorimetry. The results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Recently, Yang et al found that polydopamine (PDA) showed outstanding stability within a wide pH range, in particular after dopamine pretreatment in a moderately alkaline environment . This simple and versatile approach has since been adopted by many groups to develop new materials with applications in various research areas, such as water treatment and antifouling surface. What is more, PVA and PAA have been of great interest because of their inherent high hydrophilicity and have been adopted by many groups to prepare oil–water separation materials. PVA is not only capable of cross-linking with PAA at moderate temperatures but also is capable of self-cross-linking, which is based on esterification and etherification reactions . On the other hand, though cellulose shows great potential as the raw material used in oil–water separation because of good biodegradability, easy availability, and facile chemical modification, few works have focused on the stability of cellulose membranes used in a harsh environment.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Yang et al found that polydopamine (PDA) showed outstanding stability within a wide pH range, in particular after dopamine pretreatment in a moderately alkaline environment . This simple and versatile approach has since been adopted by many groups to develop new materials with applications in various research areas, such as water treatment and antifouling surface. What is more, PVA and PAA have been of great interest because of their inherent high hydrophilicity and have been adopted by many groups to prepare oil–water separation materials. PVA is not only capable of cross-linking with PAA at moderate temperatures but also is capable of self-cross-linking, which is based on esterification and etherification reactions . On the other hand, though cellulose shows great potential as the raw material used in oil–water separation because of good biodegradability, easy availability, and facile chemical modification, few works have focused on the stability of cellulose membranes used in a harsh environment.…”
Section: Introductionmentioning
confidence: 99%
“…Nanofiber membranes prepared by electrostatic spinning technology are widely used in the treatment of oily wastewater due to their large specific surface area, high porosity and high separation efficiency. [9][10][11] The commonly used membrane raw materials for nanofiber separation membranes are natural polymers such as cellulose, 12,13 lignin 14 and synthetic polymers such as polyacrylonitrile (PAN), [15][16][17] polyvinylidene fluoride (PVDF), 18 polyurethane (PU), 19 polyamide (PA), 20 and polyethersulfone (PES). 21 However, nanofibrous membranes prepared from these polymers suffer from poor mechanical properties, which seriously hampers their practical application space.…”
Section: Introductionmentioning
confidence: 99%